Statutes - DeJulio, Catharine; Dorsen, Norman (The Embattled Constitution, 2013)
I owe much to James Madison, that diminutive giant, one of the founding architects of our constitutional structure. In my pre-bench, academic days, much of my work focused on the challenges of governance, on the ways that our institutions operate, and on the obstacles to and steps toward the more effective functioning of government. My research and writing concentrated on a range of subjects having to do with governance, including the determinants of agency discretion,¹ and how the institutions of national government—the legislative, executive, and judicial branches—affect outcomes over time.² I viewed lawmaking as a continuum of institutional